Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai dengan Organizational Citizenship Behavior (OCB) sebagai Variabel Intervening - Rianto Hidayat Mangngi; Muh. Yamin Noch; Abdul Rasyid; Mansur (Center of Economic Students Journal, 2025)
This study aims to analyze the direct and indirect influence of Organizational Culture on Employee Performance with Organizational Citizenship Behavior (OCB) as a mediating variable. An organization's success is highly dependent on the performance of its human resources, yet the relationship between organizational culture and performance often yields inconsistent results. This research proposes OCB as a key mechanism that bridges these two variables. The research method used is quantitative with a causality approach through path analysis. The research sample consisted of 54 civil servants within the Jayapura City Regional Secretariat, selected using a simple random sampling technique. Primary data were collected through a Likert-scale questionnaire and analyzed using SPSS. The research findings show that (1) Organizational Culture has a positive and significant effect on OCB; (2) OCB has a positive and significant effect on Employee Performance; and (3) Organizational Culture does not have a significant direct influence on Employee Performance when OCB is included in the model. The Sobel test confirms that OCB fully mediates the relationship between Organizational Culture and Employee Performance (p-value = 0.00033). The implication of this finding is that to improve performance, it is not enough for management to merely build a strong culture; they must also actively encourage and facilitate the emergence of OCB among employees.